2012
DOI: 10.5732/cjc.011.10364
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor genes on frequently deleted chromosome 3p in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is among the most common malignancies in southern China. Deletion of genomic DNA, which occurs during the complex pathogenesis process for NPC, represents a pivotal mechanism in the inactivation of tumor suppressor genes (TSGs). In many circumstances, loss of TSGs can be detected as diagnostic and prognostic markers in cancer. The short arm of chromosome 3 (3p) is a frequently deleted chromosomal region in NPC, with 3p21.1–21.2 and 3p25.2–26.1 being the most frequently deleted mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 64 publications
0
47
0
1
Order By: Relevance
“…Previous studies suggested the loss of chromosomes 1p, 3p, 9p, 9q, 11q, 13q, 14q, and 16q regions are common events in NPC (13)(14)(15)(16)(17)(23)(24)(25). Functional complementation studies were performed by utilizing the microcell-mediated chromosome transfer (MMCT) approach to transfer intact or truncated chromosomes to identify the critical regions (CRs) that are important for tumor suppression in NPC cells, including 3p21.3, 14q12, 14q13.2-13.3, 14q24.1, 14q32.33, 11q13, and 11q22-23 (26)(27)(28)(29)(30)(31)(32).…”
Section: Copy Number Losses and Loss Of Heterozygosity (Loh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested the loss of chromosomes 1p, 3p, 9p, 9q, 11q, 13q, 14q, and 16q regions are common events in NPC (13)(14)(15)(16)(17)(23)(24)(25). Functional complementation studies were performed by utilizing the microcell-mediated chromosome transfer (MMCT) approach to transfer intact or truncated chromosomes to identify the critical regions (CRs) that are important for tumor suppression in NPC cells, including 3p21.3, 14q12, 14q13.2-13.3, 14q24.1, 14q32.33, 11q13, and 11q22-23 (26)(27)(28)(29)(30)(31)(32).…”
Section: Copy Number Losses and Loss Of Heterozygosity (Loh)mentioning
confidence: 99%
“…hypermethylated CpG sites. The graph is adapted from previous methylome study by Dai (13)(14)(15)(16)(17). Cyclin D1 (CCND1), located at 11q13, has the highest frequency of copy number changes in NPC, with a reported frequency ranging from 9.6% (5/52 using SNP array) to 61.9% (13/21 using aCGH) (4,18).…”
Section: Npc Mutation Hotspots In Egfr Pik3ca Kras Hras Nras Brmentioning
confidence: 99%
“…6 Frequent genetic polymorphisms and inactivation of tumor suppressor genes damage to chromosomes 3p, 5q, 13q, and 17p are predominantly regular in small cell lung carcinoma. [7][8][9][10]…”
Section: Lung Cancermentioning
confidence: 99%
“…According to the research of Dai et al, in their comparative methylome study, as the compared to nine other human cancer types, including liver, head and neck, colon, lung, thyroid, kidney, breast, pancreatic, and prostate cancer, they found that NPC had the highest hypermethylation frequency [28]. Many studies demonstrated that the inactivation of TSGs located on chromosome 3p, 9p, 9q, 11q, 13q, 14q, and 16q is the common and important events in the NPC tumorigenesis and development, as summarized in Table 1 [8,[29][30][31][32]. Representatively, the most frequently hypermethylation is reported in critical regions on chromosome 3p in NPC, as noted in Table 1.…”
Section: Lao and Lementioning
confidence: 99%